Food safety and food quality perceptions of farmers' market consumers in the United States. (September 2017) - Yu, Heyao; Gibson, Kristen E.; Wright, Kathleen G.; Neal, Jack A.; Sirsat, Sujata A.
Abstract: The number of farmers' markets in United States (U.S.) increased dramatically from 1775 markets in 1994 to 8476 markets in 2014. However, few studies have investigated consumers' food safety perceptions toward products in farmers' market or their impact on consumers' purchasing behaviors. The objectives of this study were to understand consumers' perception of food safety at farmers' markets and to explore the role of food safety perception on their purchasing fresh produce at a farmers' market. Analysis of covariance was used to investigate food safety perceptions at farmers' market among different demographic groups. In addition, multiple linear regression was used to explore factors including consumers' food safety perception and quality perception on their purchasing at a farmers' market. The results from the ANCOVA indicated that millennial generation consumers perceived better food safety conditions at farmers' markets. The linear regressions indicated quality perception and willingness to support local foods are primary reasons that consumers purchase products at farmers' markets, while food safety perception is not significantly related to purchasing fresh produce. The results imply that consumers generally hold a positive food safety perception that may be in contrast to actual microbial safety of produce obtained from farmers' markets. The results highlight an increasing need for consumer education specifically related to food safety awareness at farmers' markets. Highlights: A multi-item scale for food safety perception for farmers' market was developed. Most millennials have positive perceptions of food safety at farmers' markets. Food quality and local food support are reasons to purchase at farmers' market. Food safety perception has no significant impact on purchasing at farmers' market.